2017
DOI: 10.1007/s00262-017-1975-1
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral administration of cGAMP transiently accumulates potent macrophages for anti-tumor immunity at a mouse tumor site

Abstract: Stimulator of IFN genes (STING) spontaneously contributes to anti-tumor immunity by inducing type I interferons (IFNs) following sensing of tumor-derived genomic DNAs in the tumor-bearing host. Although direct injection of STING ligands such as cyclic diguanylate monophosphate (c-di-GMP) and cyclic [G(2',5')pA(3',5')p] (cGAMP) into the tumor microenvironment exerts anti-tumor effects through strong induction of type I IFNs and activation of innate and adaptive immunity, the precise events caused by STING in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
125
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(141 citation statements)
references
References 33 publications
9
125
1
Order By: Relevance
“…reported to display increased phagocytosis and other markers of macrophage activation; they also recruit new macrophages which serve a phagocytic role in the TME [41][42][43][44] . Consistent with these observations we confirmed that HMDMs transfected with c-di-AMP showed increased phagocytosis and exhibited elongated dendrites compared to mock-transfected populations ( Fig.…”
Section: Macrophages Exposed To Sting Agonists Delivered By Intratumomentioning
confidence: 99%
“…reported to display increased phagocytosis and other markers of macrophage activation; they also recruit new macrophages which serve a phagocytic role in the TME [41][42][43][44] . Consistent with these observations we confirmed that HMDMs transfected with c-di-AMP showed increased phagocytosis and exhibited elongated dendrites compared to mock-transfected populations ( Fig.…”
Section: Macrophages Exposed To Sting Agonists Delivered By Intratumomentioning
confidence: 99%
“…Although this result should be interpreted carefully due to low number of patients in our subgroup analysis, it may be pointed out that similar findings were observed by Aljabery et al in bladder cancer (Aljabery et al 2017). A protective effect of TAMs has been demonstrated both in vitro and in vivo (Ohkuri et al 2017). Fidler (1988) showed that activation of macrophages eliminated cancer cells and reduced metastases, but this mechanism was limited by the ratio of macrophages in relation to target cancer cells (Fidler 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, not much research has focused on CXCL11 in BC. The stimulation of IFN genes (STING) triggers macrophage production of TNFα and high expression levels of the T cell-recruiting chemokines CXCL10 and CXCL11 [50]. …”
Section: Discussionmentioning
confidence: 99%